Cognitive remediation in schizophrenia: A methodological appraisal of systematic reviews and meta-analyses. (April 2016) - Bryce, Shayden; Sloan, Elise; Lee, Stuart; Ponsford, Jennie; Rossell, Susan
Abstract: Objective: Systematic reviews and meta-analyses are a primary source of evidence when evaluating the benefit(s) of cognitive remediation (CR) in schizophrenia. These studies are designed to rigorously synthesize scientific literature; however, cannot be assumed to be of high methodological quality. The aims of this report were to: 1) review the use of systematic reviews and meta-analyses regarding CR in schizophrenia; 2) conduct a systematic methodological appraisal of published reports examining the benefits of this intervention on core outcome domains; and 3) compare the correspondence between methodological and reporting quality. Method: Electronic databases were searched for relevant articles. Twenty-one reviews met inclusion criteria and were scored according to the AMSTAR checklist-a validated scale of methodological quality. Five meta-analyses were also scored according to PRISMA statement to compare 'quality of conduct' with 'quality of reporting'. Results: Most systematic reviews and meta-analyses shared strengths and fell within a 'medium' level of methodological quality. Nevertheless, there were consistent areas of potential weakness that were not addressed by most reviews. These included the lack of protocol registration, uncertainty regarding independent data extraction and consensus procedures, and the minimal assessment of publication bias. Moreover, quality of conduct may not necessarily parallel quality of reporting, suggesting that consideration of these methods independently may be important. Conclusions: Reviews concerning CR for schizophrenia are a valuable source of evidence. However, the methodological quality of these reports may require additional consideration. Enhancing quality of conduct is essential for enabling research literature to be interpreted with confidence.